Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai - Muhammad Ridho Rizky Nanda; Putri Wahyuni (Universitas Mitra Indonesia, 2022)
This research aims to test the influence of the work environment on the performance of employees of pringsewu district office of Pringsewu regency. The data collection methods used in the study were questionnaires and interviews. The sample in the study was 35 respondents. Statistical tests are conducted using STRUCTUREL Equation Modeling based on PLS. Validity tests use loading factor values, while realibility tests use Cronbach's Alpha, composite realibility and Average Variance Extracted (AVE). The conclusion of this study is that the work environment has a positive but insignificant effect on the performance of employees of pringsewu district office of Pringsewu regency.